Fatigue Behaviour of Aluminium Tube Crimp Connections Applying the Electromagnetic Pulse Technology. (2018) - Lipp, K.; Schaefer, R.; Horwatitsch, D.
Abstract: During a still running European Project the feasibility of vehicle light weighting technologies for the manufacturing of light urban electric vehicles with new standards of mechanical performance will be demonstrated. One of the innovative technologies of the project, the Electromagnetic Pulse Technology (EMPT), which is a high speed crimping method, will be applied for joining of particular structural parts of the body, especially to join different lightweight materials such as Al- or Mg-tubes and Al- and Mg-cast or forged nodes. Current heat-intensive joining processes are faced with a number of drawbacks and "cold" classical adhesive techniques require cost-intensive preparation methods plus long curing times and show design uncertainties in terms of mechanical strength. Hence, joining of dissimilar materials is presently not widely used. The Electromagnetic Pulse Technology (EMPT) is an innovative approach for joining particular structural parts, where different lightweight materials can be joined without any significant heat input by a fast process. Therefore, this technology is determined as a high efficiency joining process from the quality and the energetic point of view, with virtually no loss of energy in form of heat. Presently, no design relevant characteristic values of such joints, neither endurable stress amplitudes (fatigue) nor stiffness behaviour of the connection during cyclic loading, are available. Hence, the reliability of such EMPT joints has to be validated with regard to fatigue and stiffness behaviour in order to guarantee a durable connection under typical service loading conditions. This paper will present first fatigue testing results for aluminium tube joints of EN AW-6082-T6 with a diameter of 40mm. Within this investigation the endurable strength and stiffness behaviour of EMPT joints will be determined in order to validate the performance of the Electromagnetic Pulse Technology for reliable applications under cyclic loading for e. g. urban electric vehicles.